Covid-19 pandemic in Brazil: Macroeconomic effects and policies - Bruno de Conti (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The Covid-19 pandemic has had unequal effects around the world, not simply in terms of health prospects, but also in terms of economic and social consequences. In all these aspects, Brazil is among the most affected countries. This article aims to analyze the economic and social effects of the Covid-19 pandemic in Brazil, as well as the main macroeconomic policies that were implemented to face the crises. To understand it properly, we take into consideration three elements: i) the structural characteristics of the Brazilian economy; ii) the economic situation in Brazil when the pandemic broke out; iii) the inefficiencies and the negligence of Bolsonaro's government. The article argues that in the public health dimension, the denialist attitude of the president resulted in a lack of national policies for social distancing and a clear mismanagement of the vaccination process which contributed to the seriousness of the crisis. As for the economic and social dimensions, the national government - after some hesitation and under the pressure of the National Congress - implemented a set of policies which have irrefutably served as a cushion for the harms of the pandemic. Nonetheless, it is crucial to underline that these policies have been insufficient to cope with the concrete urgencies of more vulnerable populations in Brazil. The intermittence and the short-termism of the fiscal programs associated with the gradual (and untimely) reduction in the benefited population and in the amounts of the transfers limited the effectiveness of the policies.
Keywords: E65; F62; I18; 330; COVID-19 pandemic; Brazil; macroeconomic policies; social policies; socioeconomic vulnerability